2017
DOI: 10.1007/s11250-017-1359-8
|View full text |Cite
|
Sign up to set email alerts
|

The first serological evidence for Rift Valley fever infection in the camel, goitered gazelle and Anatolian water buffaloes in Turkey

Abstract: Rift valley fever (RVF), a vector-borne zoonotic disease, is caused by a phlebovirus (family Bunyaviridae). The virus was initially characterized approximately 80 years ago in Kenya and disseminated to many countries in the continental Africa, Saudi Arabia, and Yemen. The infection has not been reported in Turkey. In this study, blood serum samples collected from camel (Camelus dromedairus), goitered gazelle (Gazella subgutturosa subgutturosa), and buffaloes (Bubalus bubalis linneaus) from 2000 to 2006 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…The higher prevalence reported could be attributed to the epidemics of RVF reported in these affected regions. In Sudan, [23] reported a prevalence of 9.6% in their studies and for the first time in Turkey, RVFV antibodies were reported in camels, with a prevalence of 1.3% [24]. Again, the areas in Sudan and Turkey had never experienced any epizootic of RVFV in livestock; however, antibodies were demonstrated, which may be an indication for a covert circulation waiting for the right environment for an outbreak to take place.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence reported could be attributed to the epidemics of RVF reported in these affected regions. In Sudan, [23] reported a prevalence of 9.6% in their studies and for the first time in Turkey, RVFV antibodies were reported in camels, with a prevalence of 1.3% [24]. Again, the areas in Sudan and Turkey had never experienced any epizootic of RVFV in livestock; however, antibodies were demonstrated, which may be an indication for a covert circulation waiting for the right environment for an outbreak to take place.…”
Section: Discussionmentioning
confidence: 99%
“…One camel (1.4%) and 35 buffaloes (Bubalus bubalis) (8.5%) samples were positive for RVF-specific antibodies. The positive results were detected in four different provinces of Turkey: Amasya, Ankara, Samsun and Afyon (Gur et al, 2017). In addition, Yilmaz et al (2017) detected antibodies against RVFV in 3.6%, 4.5% and 3.8% of tested children (n = 110), cattle (n = 200) and sheep (n = 160), respectively (see Section 3.1.2.3).…”
Section: Horn Of Africa Routesmentioning
confidence: 95%
“…Other examples of its transmission beyond the African mainland include its emergence in Islands of the Indian Ocean including Madagascar (69) and Mayotte (70). In addition, serological studies have suggested that RVFV may be circulating in Turkey (71) and Iran (72). To date there has been no evidence of RVFV introduction into Europe, although some researchers have speculated that this is likely based on previous examples of translocation out of Africa and a number of studies have shown that mosquito species in Europe are competent vectors for the virus (12,73).…”
Section: Rift Valley Fevermentioning
confidence: 99%